Vasilisa Maligina karya A.M. Kollontai; Sebuah rekonstruksi atas konsep maskulinitas Rusia - Elfira, Mina (Wacana, Journal of the Humanities of Indonesia, 2008)
This article is a literary analysis on Aleksandra Mikhailovna Kollontai' Vasilisa Maligina (1923) by using a feminist approach. Issues on masculinity are the focus of the analysis. The main argument of this article is that through the main character of this story - Vasilisa Maligina - Kollontai tried to expose the new image of Russian women by reconstructing the concept of Russian traditional masculinity in Russian society under former Uni Soviet communist government based on patriarchal culture.